Antimicrobial and Immunomodulatory Effect of Gum Arabic on Human and Bovine Granulocytes Against Staphylococcus aureus and Escherichia coli - Baien, Shima Hassan; Seele, Jana; Henneck, Timo; Freibrodt, Christin; Szura, György; Moubasher, Hani; Nau, Roland; Brogden, Graham; Mörgelin, Matthias; Singh, Mahavir; Kietzmann, Manfred; von Köckritz-Blickwede, Maren; et al. (Frontiers in Immunology, 2020)
Gum arabic (GA) is a traditional herbal medicine from Acacia Senegal (L) Willdenow trees, which consist of a complex mixture of polysaccharides and glycoproteins. It is used in daily applications for several diseases and is considered to protect against bacterial infections. The detailed mechanisms behind these observations are still unclear. In this study, we investigated the direct antibacterial activity of GA water and ethanol extracts against Staphylococcus (S.) aureus or Escherichia (E.) coli and the immunomodulating properties of those extracts on granulocytes as a first line of defence against bacteria. Firstly, the direct antimicrobial effect of GA was tested on three different S. aureus strains and two E. coli strains. The growth of bacteria was analysed in the presence of different GA concentrations over time. GA water as well as ethanol extracts showed a significant growth inhibition in a concentration dependent manner in case of S. aureus Newman, S. aureus Rd5 and E. coli 25922, but not in case of S. aureus USA300 and E. coli K1. Transmission electron microscopic analysis confirmed an antibacterial effect of GA on the bacteria. Secondly, the immunomodulatory effect of GA on the antimicrobial activity of bovine or human blood-derived granulocytes was evaluated. Interestingly, water and ethanol extracts enhanced antimicrobial activity of granulocytes by the induction of intracellular ROS production. In line with these data, GA increased the phagocytosis rate of E. coli. No effect was seen on neutrophil extracellular trap (NET) formation that mediates killing of extracellular bacteria such as S. aureus. In conclusion, we show that GA exhibits a direct antibacterial effect against some S. aureus and E. coli strains. Furthermore, GA boosts the antimicrobial activities of granulocytes and increases intracellular ROS production, which may lead to more phagocytosis and intracellular killing. These data might explain the described putative antimicrobial activity of GA used in traditional medicine.